Dampak Motivasi Belajar Terhadap Kehadiran Siswa SMKS Katolik Santo Ignasius Wairterang - Anastasia Nona Elcy; Agustina Irnianti Nurak; Yohanis Erwin Ngaga Dato; Advenia Disfantri Soka; Nurul Azizah; Yeremias Bardi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study analyzes the impact of learning motivation levels on student attendance discipline at the Saint Ignasius Catholic Vocational School in Wairterang. The background of the problem highlights the low level of student attendance, which is caused by the lack of intrinsic and extrinsic motivation in the vocational education environment. This phenomenon impacts the effectiveness of learning and overall student achievement. The purpose of the study is to identify the causal relationship between learning motivation and attendance discipline, and to measure the significant influence of motivation variables on attendance discipline. The approach used is quantitative with a Likert-scale questionnaire survey method. The study sample involved students in grades X-XII at the Saint Ignasius Catholic Vocational School in Wairterang, with data analysis using simple linear regression to test the hypothesis. The results of the study are expected to show a positive and significant influence of learning motivation on attendance discipline. Practical implications include recommended strategies for guidance and counseling (BK) teachers, such as individual counseling programs, attendance-based reward systems, and the integration of intrinsic motivation through vocational extracurricular activities. These strategies are expected to improve learning effectiveness and build students' disciplined character in vocational high schools